1999
DOI: 10.1086/308103
|View full text |Cite
|
Sign up to set email alerts
|

Accretion Disks around Young Objects. II. Tests of Well‐mixed Models with ISM Dust

Abstract: We construct detailed vertical structure models of irradiated accretion disks around T Tauri stars with interstellar medium dust uniformly mixed with gas. The dependence of the structure and emission properties on mass accretion rate, viscosity parameter, and disk radius is explored using these models. The theoretical spectral energy distributions (SEDs) and images for all inclinations are compared with observations of the entire population of classical T Tauri stars (CTTSs) and class I objects in Taurus. In p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
294
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(318 citation statements)
references
References 54 publications
23
294
1
Order By: Relevance
“…Recent detailed models of disk structure Ðnd that the scale height exponent varies with radius in the inner regions but follows a similar power law beyond a few AU (DÏAlessio et al 1999 ;Chiang & Goldreich 1997 ;Bell et al 1997). The scattered-light models of Burrows et al (1996) and demonstrated that high-resolution imaging enables the determination of the disk scale height at large radii.…”
Section: Disk and Stellar Structurementioning
confidence: 96%
“…Recent detailed models of disk structure Ðnd that the scale height exponent varies with radius in the inner regions but follows a similar power law beyond a few AU (DÏAlessio et al 1999 ;Chiang & Goldreich 1997 ;Bell et al 1997). The scattered-light models of Burrows et al (1996) and demonstrated that high-resolution imaging enables the determination of the disk scale height at large radii.…”
Section: Disk and Stellar Structurementioning
confidence: 96%
“…The gas density decreases radially outward as a power law of r, and in the vertical direction it decreases as z increases in roughly an exponential way. The gas heating across the disk Article published by EDP Sciences is dominated by the stellar irradiation of the surface layers at large radii (r ≥ 10 AU), thus, the kinetic temperature increases with z, while at small radii (r ∼ a few AU) viscous dissipation may become an important heating mechanism in the midplane regions (D'Alessio et al 1998(D'Alessio et al , 1999. A flared disk is significantly exposed to the strong UV field from the central star.…”
Section: Chemical Modelmentioning
confidence: 99%
“…These models assumed that a single temperature characterizes any given radius in the disk. Vertical temperature structure in the disk was Ðrst considered by Calvet et al (1991Calvet et al ( , 1992, with subsequent analysis by DÏAlessio et al (1998DÏAlessio et al ( , 1999, CG97, and CG99. In these models, absorption of stellar radiation occurs only in surface layers of the disk, while any heating due to viscous dissipation (accretion) occurs mainly in the midplane.…”
Section: Existing Disk Modelsmentioning
confidence: 99%
“…In these models, absorption of stellar radiation occurs only in surface layers of the disk, while any heating due to viscous dissipation (accretion) occurs mainly in the midplane. DÏAlessio et al (1998DÏAlessio et al ( , 1999 compute disk emission spectra assuming identical gas and dust temperature structures, whereas CG9799 essentially ignore the gas. The key issue is whether dust opacity and emissivity at the disk surface overwhelms the gas contribution at all wavelengths, in which case the gas may be ignored.…”
Section: Existing Disk Modelsmentioning
confidence: 99%
See 1 more Smart Citation